Co-targeting TMEM16A with a novel monoclonal antibody and EGFR with Cetuximab inhibits the growth and metastasis of esophageal squamous cell carcinoma - Yutian Zheng; Lin Meng; Like Qu; Chuanke Zhao; Lixin Wang; Jiayi Ma; Caiyun Liu; Chengchao Shou (Journal of Translational Medicine)
Abstract The chloride channel transmembrane protein 16A (TMEM16A) possesses a calcium-activated property linked to tumor-promoting malignant phenotype and electrophysiological stability. Numerous studies have shown that TMEM16A exhibits aberrant amplification in various squamous cell carcinomas such as esophageal squamous cell carcinoma (ESCC) and is correlated with unfavorable outcomes of ESCC patients. Therefore, TMEM16A is considered as a promising therapeutic target for ESCC. Because of its intricate structure, the development of therapeutic antibodies directed against TMEM16A has not been documented. In this study, we produced a series of novel monoclonal antibodies targeting TMEM16A and identified mT16#5 as an antibody capable of inhibiting ESCC cells migration, invasion and TMEM16A ion channel activity. Additionally, based on the validation that TMEM16A was positively correlated with expression of EGFR and the interaction between them, the mT16#5 exhibited a synergistic inhibitory effect on ESCC metastasis and growth when administered in combination with Cetuximab in vivo. In terms of mechanism, we found that mT16A#5 inhibited the phosphorylation of PI3K, AKT and JNK. These results highlight the anti-growth and anti-metastasis capacity of the combination of mT16A#5 and Cetuximab in the treatment of ESCC by targeting TMEM16A and EGFR, and provide a reference for combinational antibody treatment in ESCC.